1995
DOI: 10.1088/0268-1242/10/12/004
|View full text |Cite
|
Sign up to set email alerts
|

Photomodulated reflectivity of Zn1-xMnxTe/ZnTe multiple-quantum wells with below-bandgap excitation

Abstract: A series of Zno.93Mno.07Te/ZnTe multiple-quantum well (MQW) structures of different quantum well widths has been studied at 77 K using the conventional modulation technique of photoreflectivity (PR) with above-bandgap light providing the modulation as well as a novel version of the technique which employs below-bandgap excitation. Photoluminescence (PL) spectra of the structures are also presented. The appearance of the PR spectra obtained with below-bandgap excitation differs from that of the PR spectra with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 46 publications
(4 reference statements)
0
21
0
Order By: Relevance
“…In the BPR technique, the reflectivity of the sample is modulated by laser light whose energy is below the band gap of the semiconductor material; BPR was first reported as a new technique by Bhimnathwala and Borrego [38], although it was already applied before by Rockwell et al [39]. We have established that BPR spectra contain the same spectroscopic information as conventional photomodulated reflectivity spectra [40]. We have tried to gain some insight into the modulation mechanism of BPR and have shown that it is likely to result from the excitation of deep levels in the semiconductor material [41].…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…In the BPR technique, the reflectivity of the sample is modulated by laser light whose energy is below the band gap of the semiconductor material; BPR was first reported as a new technique by Bhimnathwala and Borrego [38], although it was already applied before by Rockwell et al [39]. We have established that BPR spectra contain the same spectroscopic information as conventional photomodulated reflectivity spectra [40]. We have tried to gain some insight into the modulation mechanism of BPR and have shown that it is likely to result from the excitation of deep levels in the semiconductor material [41].…”
Section: Introductionmentioning
confidence: 73%
“…However, the quantum dots which we have prepared are still of sizes where additional confinement effects are negligible [23], which justifies the use of the same lineshapes in the fits of the spectra for the quantum dot and the MQW samples. The choice of the lineshapes is described in great detail elsewhere [40] and is briefly summarized in the following. The change dε t for allowed excitonic transitions in the quantum well can be described by the first derivative of a complex Lorentzian lineshape with respect to transition energy E g…”
Section: Fit and Model Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each heterostructure consisted of 10 ZnTe quantum wells of thickness 80Å (sample number H561) and 100Å (H560) embedded between Zn 1−x Mn x Te barrier layers of x = 7.6 % and thickness 150Å. The samples were nominally undoped [1]. The dot samples were prepared from pieces of the two Zn 1−x Mn x Te/ZnTe MQWs by electron beam lithography for pattern definition followed by Ar 2+ ion beam etching for transferring the pattern, giving a 3.2 × 3.2 mm 2 area with a high density of homogeneous tapering pillars of height ≈ 300 nm (etching stopped before the substrate was reached) and diameter of ≈ 200 nm [4].…”
Section: Methodsmentioning
confidence: 99%
“…Photon energy of the pump beam is usually larger than the band gap of the semiconductor being under study. However, there is a possibility to use a below band gap modulation through the excitation of impurity or sur− face states [63,64]. In both cases photo−generated carriers can be trapped by surface states and in this way the surface band bending is modulated [1][2][3][4].…”
Section: Contactless Electroreflectance Vs Photo--reflectancementioning
confidence: 99%